Paleoecological Significance of Holocene Insect Fossil Assemblages from the North Coast of Alaska - Wilson, Mandy J.; Elias, Scott A. (ARCTIC, 1986)
Two peat sections containing insect fossil remains from the eastern coastal plain of the Alaskan North Slope were analyzed in comparison with pollen studies. The sections span a period from 10,400 B.P. to 1,320 B.P., providing information on the post-glacial distributions of some of the beetles species that were a part of the Beringian refugium fauna. The fossil insect evidence suggests climatic conditions similar to modern parameters, especially in the early Holocene, in general agreement with paleobotanical and vertebrate fossil interpretations for the coastal plain and elsewhere in eastern Beringia.Key words: Holocene, paleoenvironments, insect fossils, Alaska Mots clés: Holocène, paléoenvironnements, fossiles d'insectes, Alaska